Pengaruh Motivasi Kerja, Disiplin Kerja dan Komunikasi terhadap Kinerja Karyawan Melalui Kepuasan Kerja Sebagai Variabel Intervening RSUD Ujung Gading - Siskia J Adelia; Selvi Yona Sari; Della Asmaria Putri (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to find out and try to analyze. the. influe.nce. of work motivation, work discipline. and communication on e.mploye.e. pe.rformance. through job satisfaction as an inte.rve.ning variable. of Ujung Gading Hospital. This re.se.arch is a structural e.quation mode.ling (SE.M) mode.l with the. he.lp of smart PLS 3.0 analysis. The. population and sample. of this study are. e.mploye.e.s of Ujung Gading Hospital. The. re.sults of the. study showe.d a positive. and significant influe.nce. be.twe.e.n work motivation and job satisfaction. The.re. is a positive. and significant influe.nce. be.twe.e.n work discipline. and job satisfaction. The.re. was no positive. and significant influe.nce. be.twe.e.n communication and job satisfaction. The.re. is a positive. and significant influe.nce. be.twe.e.n work motivation and e.mploye.e. pe.rformance.. The.re. was no positive. and significant influe.nce. be.twe.e.n work discipline. and e.mploye.e. pe.rformance.. The.re. is no positive. and significant influe.nce. be.twe.e.n communication and e.mploye.e. pe.rformance.. The.re. is a positive. and significant influe.nce. be.twe.e.n job satisfaction and e.mploye.e. pe.rformance.. Job satisfaction is able. to me.diate. work motivation to e.mploye.e. pe.rformance.. Job satisfaction is able. to me.diate. work discipline. to e.mploye.e. pe.rformance.. Job satisfaction is not able. to me.diate. communication to e.mploye.e. pe.rformance..